The Effect of Synthetic Zeolite Admixture on the Durability of Concrete Paving Blocks - Girskas, Giedrius; Nagrockienė, Džigita; Skripkiūnas, Gintautas (The Baltic Journal of Road and Bridge Engineering, 2016)
Concrete paving blocks that were started to be used in the last century have become very popular. They became an alternative to the natural stone. Concrete paving blocks are used for the paving of pedestrian and vehicle zones. Durability is one of the main characteristics in the production of high-quality concrete paving blocks in the Baltic region climate zone. The article describes tests with concrete paving blocks, the top layer of which contains 5% of synthetic zeolite admixture obtained by means of low temperature synthesis in laboratory conditions. This zeolite admixture is obtained from aluminium fluoride production waste. The durability of concrete paving blocks was tested according to abrasion resistance, tensile splitting strength, absorption and frost resistance. The test results revealed that 5% of zeolite admixture added to the top layer of concrete paving blocks reduce the absorption, increase the tensile splitting strength by more than 10%, and decrease abrasion by 6.5%. The zeolite admixture used in concrete paving blocks reduces the scaling about 4 times after 28 freeze-thaw cycles when 3% NaCl is used as the freezing solution. The tests revealed that synthetic zeolite admixture can be used in concrete elements production by means of vibropressing (pavement elements) to increase their durability.